Ecological and epidemiological features of the distribution of toxoplasmosis in the territory of Dagestan - A. N. Dzhalilova; T. V. Tsarueva; D. N. Dzhalilova; M. S. Saidov; G. M. Gaziev; R. I. Isaeva; A. M. Kasumova; A. M. Mollaeva; B. M. Saidova (Юг России: экология, развитие)
Aim. To study the ecological and epidemiological features of the spread of toxoplasmosis in the territory of the Republic of Dagestan.Material and Methods. A total of 3152 people in the 7‐50 years age range living in Makhachkala, Kaspiysk, Derbent and rural settlements of different climatic and geographical zones of the republic, were examined for toxoplasmosis. Among those surveyed were 1817 women and 82 children. Disease with toxoplasmosis was diagnosed according to laboratory and clinical and epidemiological data. Of the serological research methods, RIF (immunofluorescence reaction) and ELISA (enzyme‐linked immunosorbent assay) were used. Based on the survey results, ecological and epidemiological maps were compliedResults. It was revealed that the inhabitants of lowlands are 1,7 times more likely to be infected with toxoplasmosis than mountain settlements. The unequal frequency of toxoplasmosis infection in residents of mountainous and foothill areas depends not only on the altitude of the area above sea level, but also on soil moisture (plains and foothills), the intensity of isolation (highlands), as well as contact with infected domestic and agricultural animals. Infection with toxoplasma invasion in different territories varied within the range of 17.3%‐29.1%.Conclusion. Identification of the sources of toxoplasma invasion was undertaken structured around regionally‐oriented methods for the prevention of the disease. Typifying the sources of toxoplasmosis included monitoring: levels of sanitation when in contact with insufficiently thermally processed food products; obligatory hand washing after working with the soil; contact with pets; special sanitary and veterinary control over persons in contact with animals, as well as sanitary and medical care of patients and pregnant women.